The role of B cells in COVID-19 infection and vaccination - Chen, Shiru; Guan, Fei; Candotti, Fabio; Benlagha, Kamel; Camara, Niels Olsen Saraiva; Herrada, Andres A.; James, Louisa K.; Lei, Jiahui; Miller, Heather; Kubo, Masato; Ning, Qin; Liu, Chaohong (Frontiers in Immunology, 2022)
B cells secrete antibodies and mediate the humoral immune response, making them extremely important in protective immunity against SARS-CoV-2, which caused the coronavirus disease 2019 (COVID-19) pandemic. In this review, we summarize the positive function and pathological response of B cells in SARS-CoV-2 infection and re-infection. Then, we structure the immunity responses that B cells mediated in peripheral tissues. Furthermore, we discuss the role of B cells during vaccination including the effectiveness of antibodies and memory B cells, viral evolution mechanisms, and future vaccine development. This review might help medical workers and researchers to have a better understanding of the interaction between B cells and SARS-CoV-2 and broaden their vision for future investigations.